Risk Factors for Candidemia After Open Heart Surgery: Results From a Multicenter Case–Control Study. (19th June 2020) - Giacobbe, Daniele Roberto; Salsano, Antonio; Del Puente, Filippo; Miette, Ambra; Vena, Antonio; Corcione, Silvia; Bartoletti, Michele; Mularoni, Alessandra; Maraolo, Alberto Enrico; Peghin, Maddalena; Carnelutti, Alessia; Losito, Angela Raffaella; et al.
Abstract: Background: Candida species are among the most frequent causative agents of health care–associated bloodstream infections, with mortality >40% in critically ill patients. Specific populations of critically ill patients may present peculiar risk factors related to their reason for intensive care unit admission. The primary objective of the present study was to assess the predictors of candidemia after open heart surgery. Methods: This retrospective, matched case–control study was conducted in 8 Italian hospitals from 2009 to 2016. The primary study objective was to assess factors associated with the development of candidemia after open heart surgery. Results: Overall, 222 patients (74 cases and 148 controls) were included in the study. Candidemia developed at a median time (interquartile range) of 23 (14–36) days after surgery. In multivariable analysis, independent predictors of candidemia were New York Heart Association class III or IV (odds ratio [OR], 23.81; 95% CI, 5.73–98.95; P < .001), previous therapy with carbapenems (OR, 8.87; 95% CI, 2.57–30.67; P = .001), and previous therapy with fluoroquinolones (OR, 5.73; 95% CI, 1.61–20.41; P = .007). Crude 30-day mortality of candidemia was 53% (39/74). Septic shock was independently associated with mortality in the multivariable model (OR, 5.64; 95% CI, 1.91–16.63; P = .002). No association between prolonged cardiopulmonary bypass time and candidemia was observed in this study. Conclusions: Previous broad-spectrum antibiotic therapy and high NYHA class were independent predictors of candidemia in cardiac surgery patients with prolonged postoperative intensive care unit stay.